Role of Local Governments in Preventing and Treating Victims of Human Trafficking - Faisal Fadilla Noorikhsan; Hilal Ramdhani; Nisa Khoerunisa (Universitas Medan Area, 2022)
This study aims to find the concept of prevention and treatment for citizens related to human trafficking carried out by local governments. Empirically, the problem of human trafficking is a violation of human rights related to the right to personal freedom. The majority of these crimes afflict vulnerable groups, such as women and children. On this basis, this study uses a qualitative approach with a descriptive method. The data in this study were taken using in-depth interviews, observation, and documentation techniques. This study uses a constructivist perspective, which is to build ideas through data so as to produce a complete picture. The results show that the model for preventing and handling human trafficking must be collaborative with the central government and institutions dealing with human trafficking issues at the local level. An important aspect that local governments need to focus on is obtaining valid data on maps of human trafficking problems in their administrative areas. This will support efforts to prevent and handle victims of human trafficking involving government and non-government elements. An important aspect of the model for preventing and dealing with human trafficking is that local governments need to increase public participation in campaigning against human trafficking.